The masonry calculation strength under the vertical and horizontal loads combined action by the variational method in the plasticity theory (Academic journal Industrial Machine Building Civil Engineering, 2022)
Possible causes of destruction of masonry in buildings with bearing masonry walls under the combined effect of vertical and horizontal loads are considered. The diagonal shear is highlighted as a typical case for partitions under seismic impacts. Based on the analysis of the results of experimental studies of samples for skewing, as models of the operation of the partition, proposals are presented for a kinematically possible scheme of the masonry elements destruction, which is proposed as a base for the calculation. The strength problem was solved by the variational method in the theory of plasticity, taking into account both strength characteristics of the masonry, the dimensions of the samples, and the loading areas. The peculiarities of the masonry work are taken into account by using the appropriate strength condition. The influence on the strength of reinforcement of masonry partitions during diagonal splitting is considered.
Keywords: partition; seismic impact; diagonal splitting; plastic strain